Neuroprotection of N-benzyl Eicosapentaenamide in Neonatal Mice Following Hypoxic–Ischemic Brain Injury - Mengya Jiao; Qun Dong; Yiting Zhang; Min Lin; Wan Zhou; Tao Liu; Baohong Yuan; Hui Yin (Molecules, 2021)
Maca (Lepidium meyenii) has emerged as a popular functional plant food because of its medicinal properties and nutritional value. Macamides, as the exclusively active ingredients found in maca, are a unique series of non-polar, long-chain fatty acid N-benzylamides with multiple bioactivities such as antifatigue characteristics and improving reproductive health. In this study, a new kind of macamide, N-benzyl eicosapentaenamide (NB-EPA), was identified from maca. We further explore its potential neuroprotective role in hypoxic–ischemic brain injury. Our findings indicated that treatment with biosynthesized NB-EPA significantly alleviates the size of cerebral infarction and improves neurobehavioral disorders after hypoxic–ischemic brain damage in neonatal mice. NB-EPA inhibited the apoptosis of neuronal cells after ischemic challenge. NB-EPA improved neuronal cell survival and proliferation through the activation of phosphorylated AKT signaling. Of note, the protective property of NB-EPA against ischemic neuronal damage was dependent on suppression of the p53–PUMA pathway. Taken together, these findings suggest that NB-EPA may represent a new neuroprotectant for newborns with hypoxic–ischemic encephalopathy.